PERANCANGAN KAPAL GENERAL CARGO 5500 DWT KECEPATAN 11 KNOT DENGAN RUTE PELAYARAN TANJUNG PERAK (SURABAYA) - PELABUHAN SAMARINDA (SAMARINDA) - Fieki Adinta Karunia Yosafat, (2020)
Surabaya, which is the center of the city in the province of East Java, is a place of business in inter-city and overseas export-import activities in meeting the needs of the community in maintaining the economy in the Surabaya area. Meanwhile, Samarinda, which is in East Kalimantan, is one of the provinces to develop the economic wheels in Indonesia. Surabaya, which is an onion producing province in Indonesia, and Samarinda, which produces cement in Indonesia, help each other in meeting the needs of the people in their respective regions. Therefore a General Cargo ship is needed to deliver goods. The General Cargo ship that will be designed will use a crane as ship loading and unloading equipment. The main dimensions of the design ship were obtained using the 2 comparator method, and the authors took 2 comparative ship sample data from Bureau Veritas (Register France). In this thesis, the authors designed a General Cargo ship with a speed of 11 knots with the shipping route of the Port of Tanjung Perak (Surabaya) - Samarinda Port (Samarinda) with the principal size obtained LOA: 92.7 m, LPP: 88.07 m, B: 14 , 62 m, H: 7.53 m, T: 6.45m, with a dead weight of 5500 DWT. And there are rules in the making of this flow thesis.